Chrononutrition is associated with melatonin and cortisol rhythm during pregnancy: Findings from MY-CARE cohort study - Teoh, Ai Ni; Kaur, Satvinder; Shafie, Siti Raihanah; Mohd Shukri, Nurul Husna; Ahmad Bustami, Normina; Takahashi, Masaki; Shibata, Shigenobu (Frontiers in Nutrition, 2023)
Chrononutrition has been suggested to have an entrainment effect on circadian rhythm which is crucial for metabolic health. Investigating how chrononutrition affects maternal circadian rhythm can shed light on its role during pregnancy. This study aims to determine chrononutrition characteristics of healthy primigravida during pregnancy and its association with melatonin and cortisol rhythm across gestation. A total of 70 healthy primigravidas were recruited from ten randomly selected government maternal and child clinics in Kuala Lumpur, Malaysia. During the second and third trimesters, chrononutrition characteristics including meal timing, frequency, eating window, breakfast skipping, and late-night eating were determined using a 3-day food record. Pregnant women provided salivary samples at 5 time-points over a 24h period for melatonin and cortisol assay. Consistently across the second and third trimesters, both melatonin and cortisol showed a rhythmic change over the day. Melatonin levels displayed an increment towards the night whilst cortisol levels declined over the day. Majority observed a shorter eating window (≤12 hours) during the second and third trimesters (66% and 55% respectively). Results showed 23% and 28% skipped breakfast whereas 45% and 37% ate within 2 hours pre-bedtime. During the third trimester, a longer eating window was associated with lower melatonin mean (β=-0.40, p=0.006), peak (β=-0.42, p=0.006), and AUCG (β=-0.44, p=0.003). During both trimesters, a lower awakening cortisol level was observed in pregnant women who skipped breakfast (β=-0.33, p=0.029; β=-0.29, p=0.044). Only during the second trimester, breakfast-skipping was significantly associated with a greater cortisol amplitude (β=0.43, p=0.003). Findings suggest that certain chrononutrition components, particularly eating window and breakfast skipping have a significant influence on maternal melatonin and cortisol rhythm. Dietary intervention targeting these characteristics may be useful in maintaining maternal circadian rhythm.